Syk-Targeted, a New 3-Arylbenzofuran Derivative EAPP-2 Blocks Airway Inflammation of Asthma–COPD Overlap in vivo and in vitro - Li S; Hui Y; Yuan J; Zhang Z; Li X; Fang N; Lin M; Hou Q (Dove Medical Press, 2021)
Shuyi Li, Yang Hui, Jiqiao Yuan, Ziqian Zhang, Xuyu Li, Nan Fang, Mingbao Lin, Qi Hou Institute of Materia Medica, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Mingbao Lin; Qi Hou Tel +86-10-63165192; +86-10-63165191Email mingbaolin@imm.cams.cn; houq@imm.ac.cnIntroduction: Asthma–chronic obstructive pulmonary (COPD) overlap (ACO) coexists with asthma and COPD syndrome characteristics, with more frequent exacerbations, heavier disease burden, higher medical utilization, and even lower quality of life. However, the ACO standard medications supported by evidence-based medicine have not yet appeared.Methods: By using an ACO mouse model established previously and LPS-stimulated RAW264.7 macrophages in vitro, a potential therapeutic candidate, EAPP-2, was screened from derivatives of 3-arylbenzofuran, and its effect and mechanism on ACO inflammation were evaluated.Results: EAPP-2 significantly alleviated airway inflammation in ACO mice and also inhibited the inflammatory reactions in LPS-induced RAW264.7 macrophages in vitro. Furthermore, EAPP-2 significantly inhibited the expression and phosphorylation of spleen tyrosine kinase (Syk), a common target regulating both eosinophils and neutrophils inflammation. In addition to this, EAPP-2 significantly down-regulates the expression of NF-κB, p-NF-κB, and NLRP3 in vivo and in vitro. Moreover, by using specific inhibitors in vitro, it was validated that EAPP-2 targeted on Syk and then regulated its downstream NF-κB and NLRP3.Conclusion: EAPP-2 is shown to be a potentially useful therapeutic candidate for ACO, and its mechanism is at least partially achieved by targeting on Syk and then inhibiting NF-κB or NLRP3. Moreover, this study suggests that Syk may be a potentially effective target for ACO therapy.Keywords: EAPP-2, asthma–COPD overlap, ACO, Syk, NF-κB, NLRP3